Effects of self and cross pollination on fruit set and fruit quality of sour cherry cultivars - Ansari, M.; Davarynejad, G. H.; Tornyai, J.; Nyéki, J.; Szabó, Z.; Soltész, M. (International Journal of Horticultural Science, 2010)
An experiment conducted using factorial based on randomized completely block design during 2005 and 2006. Flowers of Érdi bőtermő, Érdi jubileum and Cigány meggy before anthesis and in balloon stages were isolated with paper bags from guest pollens and pollinated in appropriate time. The averages of final fruit set showed the advantage of open pollination (14.6% fruit set) in compare with artificial self pollination (13.0% fruit set) and natural self pollination (4.4% fruit set). Siah mashhad sweet cherry cultivar with more than 70% overlap of flowering and 9.8% fruit set in 2005 and 17.9% in 2006 was the best among applied pollinisers for Érdi bôtermô sour cherry cultivar.Also, Siah mashhad sweet cherry with more than 50%overlap of flowering time and 25.8%fruit set was the best polliniser for Cigány megg. Among the pollinisers, Siah mashhad was the best for Érdi jubileum with more than 50% overlap and 15.22% fruit set. Meanwhile, pollens of Siah mashhad caused the increase of fruit size in Cigány meggy cultivar. phenomenon. Pollens of Siah mashhad caused reduction in total soluble solids of Érdi bôtermô fruits, however, it does not have any significant effect on the acid rate of fruits.